2019
DOI: 10.1088/1757-899x/536/1/012086
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Gum Arabic as Surfactant on the Stability of Water-based Alumina Nanoparticle Suspensions

Abstract: The stability study of alumina nanoparticle suspensions has been investigated by using gum arabic as a surfactant. The effect of particle volume fraction of alumina nanoparticle and gum arabic concentration were observed. The stability of the suspension was characterized using zeta potential and particle size distribution analysis. Several volume fractions of alumina and gum arabic concentration were dispersed in water as a solvent for suspension stability. The result showed that the stability of water-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results reveal that the nanofluid with less concentration of stability of ZnO is much more stable than the samples with high concentration of ZnO in the base fluid. This is happened due to the mechanism of Brownian motion at high concentration the when the ZnO nanoparticles tend to agglomerate and they are settled after short time, in agreement with Irwan et al [16]. The obtained values are in the range of -30 to -40 mV for Tx-100 and in the range of -48 to -55 mV for GA.…”
Section: Zeta Potentialsupporting
confidence: 88%
See 1 more Smart Citation
“…The results reveal that the nanofluid with less concentration of stability of ZnO is much more stable than the samples with high concentration of ZnO in the base fluid. This is happened due to the mechanism of Brownian motion at high concentration the when the ZnO nanoparticles tend to agglomerate and they are settled after short time, in agreement with Irwan et al [16]. The obtained values are in the range of -30 to -40 mV for Tx-100 and in the range of -48 to -55 mV for GA.…”
Section: Zeta Potentialsupporting
confidence: 88%
“…Also, we mention the researches of Anand and Siby [15] about the effect of four different surfactants (Triton Tx-100, polyethylene glycol (PEG 6000), cetyltrimethylammonium bromide (CTAB), SDS) added into a zinc oxide / water base fluid. Irwan et al [16] have used Gum Arabic as surfactant to study the stability of Al2O3/ water nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…The negative zeta potential value was owing to the presence of –COO − and –OH ions as a result of dissociation of carboxyl groups (Benmounah et al, 2017), and the smaller particle size of Sangri gum reduces the interaction of the particles to agglomerate thereby providing good stability. Zeta potential of Sangri gum was comparable with that of gum Arabic: −25.7 mV (Nurdin et al, 2019) and guar gum: −30.05 mV (Kaur & Kaur, 2018). Along with increased concentration of the gum, the stability can be further improved which is reflected in the following emulsification studies of Sangri gum.…”
Section: Resultsmentioning
confidence: 82%
“…7844 19894-97-4 2 Naphthalene, 1,2,3,5,6,8a-hexahydro-4,7-dimethyl- the postharvest application of GA with and without Cinnamon and Lemon Grass EOs on some tropical fruits as a shelf life enhancer, they concluded that GA with EOs gave fruits high protection and prolonged their storage period, which is supporting the present research findings. Nurdin et al (2019) used GA as a surfactant on the stability of water-based alumina nanoparticle suspension and concluded that when the concentration of GA increased (from 0.1% to 0.5%) the zeta potential falls down (from -25mV to -36mV). Hence, this could be explained that GA minimizes interaction between particles which in turn prevents the suspension from agglomeration.…”
Section: Resultsmentioning
confidence: 99%